(y−1)dx−(x−y−1)dy=0
"(y-1)dx-(x-y-1)dy=0\\\\\nM=y-1 \\implies M_y=1\\\\\nN=-(x-y-1) \\implies N_x=-1\\\\\n\\text{Thus } M_y\\neq N_x \\implies \\text{ It is not exact}\\\\\n\\text{To get the integrating factor;}\\\\\n\\frac{N_x-M_y}{M}=-\\frac{2}{y-1}. \\\\\nI.F=e^{\\int -\\frac{2}{y-1}dy}=e^{-2\\ln (y-1)}=(y-1)^{-2}\\\\\n\\text{Multiply the DE by I.F}\\\\\n(y-1)^{-1}dx-\\frac{x-y-1}{(y-1)^2}dy=0\\\\\nM_y=N_x=-\\frac{1}{(y-1)^2}\\\\\nF_x=(y-1)^{-1}dx\\\\\nF=\\int(y-1)^{-1}dx\\\\\nF=x(y-1)^{-1}+\\Phi(y)\\\\\n\\text{Differentiate w.r.t y}\\\\\nF_y=-\\frac{x}{(y-1)^2}+\\Phi'(y)\\\\\n-\\frac{x-y-1}{(y-1)^2}=-\\frac{x}{(y-1)^2}+\\Phi'(y)\\\\\n\\Phi'(y)=-\\frac{y+1}{(y-1)^2}\\\\\n\\Phi(y)=\\frac{2}{y-1}-\\ln(y-1)\\\\\n\\text{Hence}\\\\\nF=x(y-1)^{-1}+\\frac{2}{y-1}-\\ln(y-1)"
Comments
Leave a comment